DEVELOPMENT OF TOLERANCE STUDENTS BASED ON NATIONAL TRADISHIONS AND THE HISTORY OF EASTERN CULTURE - Yuldasheva Mashkhura Muzafarovna (International Journal of Innovations in Engineering Research and Technology, 2022)
The article examines the development of tolerance among medical students on the basis of national traditions, reveals the main approaches to educating young people in the spirit of tolerance, humanity, the formation of high spirituality, culture and creative thinking in students, instilling in young people a desire for knowledge, the need for self-improvement today is more important than ever. The peoples of Central Asia and the Middle East have a long history of tolerance, that our ancestors from an early age were tolerant of other religions and nationalities, instilled in them such qualities as respect for the culture, language and traditions of other peoples. At the same time, it was said that the education of tolerance is also passed on to future generations.